Measuring anxiety in the elderly : a thesis presented in partial fulfillment of the requirements for the degree of Masters of Science in Psychology at Massey University - Pack, Jethro (Massey University, 2006)
The present study investigated the measurement of anxiety across age, with particular attention being paid to old older adults (75+ years). Comparisons of scores from the Beck Anxiety Inventory (BAI), trait scale of the State-Trait Anxiety Scale (STAI-t), and the Adult Manifest Anxiety Scale for the Elderly (AMAS-E) were made across three age groups: Adult (35-54), Young older (55-74), and Old older (75+). The relationship between anxiety and depression was also investigated with the inclusion of the Beck Depression Inventory (BDI) and Geriatric Depression Scale (GDS) for comparison with the anxiety measures. It was found that BAI scores increased with age, with older adults having mean scores near the mild anxiety cutoff. The BAI also had poor correlations with, and different standardized scores to, other anxiety measures, indicating poor construct validity for the BAI with this non-clinical sample. The BDI poorly correlated with the GDS and with anxiety measures with Old older adults, indicating that it may not be the effective measure it is with younger adults. The present findings suggest that the presentation of anxiety may be different in adults over 75 years old compared to younger adults. Furthermore, some of the current self-report measures that are commonly used in clinical practice and research are not as effective assessment tools with this age group as they are with younger groups.
Keywords: Anxiety; Anxiety in old age